GE11 peptide conjugated selenium nanoparticles for EGFR targeted oridonin delivery to achieve enhanced anticancer efficacy by inhibiting EGFR-mediated PI3K/AKT and Ras/Raf/MEK/ERK pathways - Pi, Jiang (Drug Deliv, 2017)
Selenium nanoparticles (Se NPs) have attracted increasing interest in recent decades because of their anticancer, immunoregulation, and drug carrier functions. In this study, GE11 peptide-conjugated Se NPs (GE11-Se NPs), a nanosystem targeting EGFR over-expressed cancer cells, were synthesized for oridonin delivery to achieve enhanced anticancer efficacy. Oridonin loaded and GE11 peptide conjugated Se NPs (GE11-Ori-Se NPs) were found to show enhanced cellular uptake in cancer cells, which resulted in enhanced cancer inhibition against cancer cells and reduced toxicity against normal cells. After accumulation into the lysosomes of cancer cells and increase of oridonin release under acid condition, GE11-Ori-Se NPs were further transported into cytoplasm after the damage of lysosomal membrane integrity. GE11-Ori-Se NPs were found to induce cancer cell apoptosis by inducting reactive oxygen species (ROS) production, activating mitochondria-dependent pathway, inhibiting EGFR-mediated PI3K/AKT and inhibiting Ras/Raf/MEK/ERK pathways. GE11-Se NPs were also found to show active targeting effects against the tumor tissue in esophageal cancer bearing mice. And in nude mice xenograft model, GE11-Ori-Se NPs significantly inhibited the tumor growth via inhibition of tumor angiogenesis by reducing the angiogenesis-marker CD31 and activation of the immune system by enhancing IL-2 and TNF-α production. The selenium contents in mice were found to accumulate into liver, tumor, and kidney, but showed no significant toxicity against liver and kidney. This cancer-targeted design of Se NPs provides a new strategy for synergistic treating of cancer with higher efficacy and reduced side effects, introducing GE11-Ori-Se NPs as a candidate for further evaluation as a chemotherapeutic agent for EGFR over-expressed esophageal cancers.